Denosumab for the treatment of osteoporosis. (March 2015) - Zaheer, Sarah; LeBoff, Meryl; Lewiecki, E Michael
<x xml:space="preserve">Abstract</x> Introduction: Low trauma fractures due to osteoporosis are a major health concern worldwide. Despite the availability of many therapeutic compounds to reduce fracture risk, osteoporosis remains undertreated and the burden of osteoporotic fractures remains high. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Denosumab&logicalOpe1=OR&field2=articletitle&text2=Denosumab&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Denosumab is a novel agent that acts to reduce bone turnover, improve bone mineral density, and reduce fracture risk, offering a favorable efficacy and safety profile. Areas covered: This review covers the pharmacology and major clinical trials with extension/post-marketing follow-up, including trials for all FDA-approved indications of denosumab to date. Expert opinion: Denosumab is an efficacious and safe osteoporosis treatment option, with current data from up to 8 years of continued use showing continued improvement in bone density with sustained fracture risk reduction. Safety profiles overall are similar to placebo, with no new safety concerns in extension trials, though a theoretical increased risk of infection exists with RANKL inhibition. Future considerations include safety of prolonged treatment beyond 8 years, and efficacy/fracture risk after discontinuation or with non-adherence, given the characteristic pharmacodynamic profile of denosumab.